2020
DOI: 10.3390/f11080795
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evidence for Domestication Effects on the Genetic Diversity of Guazuma crinita in the Peruvian Amazon

Abstract: Guazuma crinita, a fast-growing timber tree species, was chosen for domestication in the Peruvian Amazon because it can be harvested at an early age and it contributes to the livelihood of local farmers. Although it is in an early stage of domestication, we do not know the impact of the domestication process on its genetic resources. Amplified fragment length polymorphic (AFLP) fingerprints were used to estimate the genetic diversity of G. crinita populations in different stages of domestication. Our objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
3
4
0
4
Order By: Relevance
“…In addition, this is expected in this species, because it produces seeds that are dispersed over long distances by wind and water. In general, this is the case of tropical trees, and especially those that are outcrossing, and pollinated and/or dispersed by wind, so they tend to harbor high levels of genetic diversity at local and regional spatial scales [24]. Moreover, our results are in agreement with similar studies by Russell et al [1] and Tauchen et al [3].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, this is expected in this species, because it produces seeds that are dispersed over long distances by wind and water. In general, this is the case of tropical trees, and especially those that are outcrossing, and pollinated and/or dispersed by wind, so they tend to harbor high levels of genetic diversity at local and regional spatial scales [24]. Moreover, our results are in agreement with similar studies by Russell et al [1] and Tauchen et al [3].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, although genetic relationship between species is relatively low using those markers (low Nei´s index), the diversity of the sequences and therefore of the population is relatively high (high Simpson and Shannon indices) [22,23]. Similarly, a recent study on Guazuma crinita reported low Nei´s gene diversity and high Shannon information index [24]. In addition, our expected heterozygosity is similar to the populations of tornillo (Cedrelinga cateniformis) [16].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Nei's genetic diversity index ranged from 0.12 to 0.41, indicating high genetic diversity, which is concordant for specimens from natural populations as they are not affected by artificial selection. Maintaining high genetic diversity in natural populations is important because it reduces the risk of local extinction under natural conditions [50,51]. Similarly, the Shannon-Wiener index is slightly high (1.79 to 2.94) and demonstrates the wealth and abundance among capirona clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Bolaina blanca (Guazuma crinita Mart, Meliaceae) es una especie forestal maderable de rápido crecimiento que se desarrolla en bosques aluviales de la Amazonía Peruana (Tuisima-Coral et al, 2020). Posee excelentes propiedades físicas, mecánicas y estéticas, razón por la cual viene siendo utilizada en la obtención de madera rolliza y aserrada para la fabricación de parihuelas, cajonería, laminado, juguetería, palos de fósforo, paletas de consultorios médicos, chupetes, palitos de helados, artesanía, tableros contrachapados, entre otros (IIAP, 2009;Basauri et al, 2019).…”
Section: Introductionunclassified